Pengaruh Strategi Koping Terhadap Tingkat Kecemasan Pada lanjut Usia (Lansia) Hipertensi di Puskesmas Tamalate Kota Makassar - Marliana Marliana; Andi Asrina; Arman Arman (PT.Mantaya Idea Batara, 2024)
In old age, body function has declined. One of the conditions experienced by Lanisa is hypertension, which can lead to mental problems in the elderly because the higher the hypertension, the more they feel afraid and anxious about their condition. Therefore, it is a needed strategy for coping. This study aimed to discover the influence of problem-focused coping dan emotion-focused coping on anxiety levels in hypertension old ages (elderly) at Tamalate Community Health, Makassar City. This study is quantitative with Cross Sectional Study design. Techniq The sampling technique is purposive sampling, and the number of samples is 154. Data analysis used a statistical test (t-test) with a significance level of 95% (?: 0.05). The research showed Problem-Focused Coping to anxiety level P-Value is 0,009 and a B value is -0.345. Emotion Focused Coping for anxiety level at P value 0,000 and B value 0,275. In conclusion, problem-focused coping has influenced anxiety levels in hypertension elderly and direction a negative influence. The emotion-focused coping influenced anxiety levels in hypertension elderly and direction positively influenced.